Establishment Of Micropropagation Protocol For Banana (Musa Acuminata X M. Balbisiana) CV. Pisang Awak (ABB Genome) Via Temporary Immersion System - Au , Vun Hui (2011)
Two surface-sterilization protocols were established to obtain aseptic shoot explants of Pisang Awak for micropropagation purpose. Aseptic explants could be established from one day old suckers by using one-stage surface-sterilization method with 20% (v/v) Clorox® for 20 minutes. Two-stage surface-sterilization technique could be used for more than one day old suckers.